High-Pressure Injection Injuries of the Hand: Our Experience and Literature Review - Jayachandiran, Anand Prasath; Ananthappan, Manoj; Divya, Vasireddy; Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Rajendran, Suresh (Indian Journal of Plastic Surgery, 2025)
High-pressure injection injuries are serious and often underestimated traumas that can lead to severe soft tissue damage, ischemia, infection, and even amputation. These injuries commonly occur in industrial settings, particularly affecting young male workers handling chemicals.Seven male patients with high-pressure hand injection injuries from November 2019 to December 2024 were evaluated retrospectively. Immediate debridement and broad-spectrum antibiotics were administered. Follow-up assessed the recovery and functional outcomes.Out of seven patients, one was managed conservatively and the others required multiple debridements, with two presenting with infections and one with compartment syndrome. X-rays confirmed the presence of foreign bodies in all cases. Soft tissue defects were addressed using reconstructive techniques. One patient developed finger stiffness, and two were lost to follow-up. In most cases, aggressive early intervention and debridement reduced infection and preserved hand function, although some patients experienced prolonged recovery due to tissue loss and the need for flap coverage.High-pressure injection injuries require rapid recognition and management, as delays increase the risk of infection, necrosis, and functional impairment. Early, thorough debridement is essential, especially with materials like paint thinner significantly elevating the risk of amputation. This study emphasizes educating emergency physicians on early recognition and intervention for optimal outcomes.
Keywords: hand; high pressure; injection injury